Cases of Impaired Oxidative Burst in HIV-Exposed Uninfected Infants’ Neutrophils—A Pilot Study - Maloupazoa Siawaya, Anicet Christel; Mveang-Nzoghe, Amandine; Mvoundza Ndjindji, Ofilia; Mintsa Ndong, Armel; Essone, Paulin N.; Djoba Siawaya, Joel Fleury (Frontiers in Immunology, 2017)
An increased risk of serious bacterial infections in HIV exposed uninfected (HEU) infants has been demonstrated. Although neutrophils are essential for the protection of infants against bacterial infections, no study has investigated their profile in HEU infants to date. In this study, we assessed the function of neutrophils in HEU infants using the Nitroblue tetrazolium (NBT) reduction test. Among 25 HEU infants, 9 (36%) showed a reduced ability of their neutrophils to produce Reactive Oxygen Species (ROS) upon stimulation with bacteria. No alteration of total neutrophil counts was noted in the blood of HEU infants indicating that the alteration observed in the 36% of HEU infants may only be functional. Conclusively, impaired neutrophil function could be a factor of vulnerability in HEU infants.